Assessing the performance of a versatile and affordable geotechnical monitoring system for river embankments. (June 2020) - Rocchi, Irene; Gragnano, Carmine Gerardo; Govoni, Laura; Bittelli, Marco; Gottardi, Guido
Abstract: River embankments stability is a key aspect in geohazard assessment and underestimating its failure risk may result in unexpected and severe damages. Changes in hydraulic and climatic boundary conditions are responsible for transient water flow within the embankments, consequently the related soil water content and pore-water pressure distributions vary with time. Therefore, it is crucial to investigate their hydraulic and retention behaviour in order to assess in a reliable way the safety margins towards instability mechanisms. To obtain a realistic estimate of key variables in time and space, as a function of external conditions, a combination of field measurements, laboratory testing and suitably calibrated numerical analyses should be used. To achieve this purpose, a full-scale monitoring system was implemented on a cross section of an embankment along the river Secchia (Modena, Italy), mainly measuring the pore-water pressure (including suction) and the water content at different depths. A relatively large variety of different sensors have been installed, to compare their performance in terms of robustness and reliability, and collected data have been interpreted with the help of laboratory and field geotechnical characterisation. The article describes such system and the sensors used, their capabilities and the installation techniques, resulting in quite innovative solutions for the specific application. The spatial variability of the monitored variables is also finally presented and discussed. The proposed integrated monitoring system, which aims at making use of affordable and commercially available sensors that can be therefore installed along extensive river stretches, appears a fundamental starting point to assess potential risks of such geotechnical infrastructures in real-time and to devise well-balanced related mitigation measures. Highlights: Design and implementation of a full-scale monitoring system in a river embankment. Pore pressure/suction and water content measured during seepage to significant depth. Monitoring data collected for a period of 2 years are showed and discussed. Smooth changes with depth and similar retention behaviour despite soil heterogeneity. Spatial distribution of pore pressure/suction is estimated using site measurements.